2011
DOI: 10.1007/s00432-011-1043-8
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells are associated with response to chemotherapy in human non-small-cell lung cancer

Abstract: Peripheral blood levels of bone marrow-derived EPCs are significantly increased in patients with NSCLC and correlate with response to chemotherapy. EPCs may offer a possible biomarker for efficient of treatment and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…In our study, patients with a high CEC count at baseline had a significantly worse PFS and OS. A majority of reports showed that high baseline CEC levels above the 75th percentile significantly correlated with prognosis, and could be useful as prognostic markers in patients with advanced NSCLC (Fleitas et al , 2010; Morita et al , 2011; Wang et al , 2013). In contrast, a study of 31 patients with advanced NSCLC treated with first-line carboplatin and paclitaxel reported that a CEC count of >400/4 ml at baseline showed a significantly improved PFS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with a high CEC count at baseline had a significantly worse PFS and OS. A majority of reports showed that high baseline CEC levels above the 75th percentile significantly correlated with prognosis, and could be useful as prognostic markers in patients with advanced NSCLC (Fleitas et al , 2010; Morita et al , 2011; Wang et al , 2013). In contrast, a study of 31 patients with advanced NSCLC treated with first-line carboplatin and paclitaxel reported that a CEC count of >400/4 ml at baseline showed a significantly improved PFS.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization demonstrated that CXCR7 mRNA was confined to the vascular endothelium at the depths of glial cell tumours, where CXCL12 was concentrated (Odemis et al, 2012). Furthermore, CXCR7 plays an important role in human cord blood derived EPCs in response to CXCL12 by inducing EPCs adhesion to active umbilical vein endothelial cells and trans-endothelial migration (Burns et al, 2006;Morita et al, 2011;Tseng et al, 2011). In the present study, CXCR7 mRNA was detected in hemangioblastoma, but significantly lower than that in brain tissues from patients with neurilemmoma or meningioma, which was not found before.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF), which is secreted by rhabdomyosarcoma (RMS), is an autocrine/ paracrine factor that interacts with CXCR4 as well as with CXCR7 to enhance the adhesiveness of RMS cells (Tarnowski et al, 2010). EPCs may offer a possible biomarker for efficient of treatment and prognosis (Morita et al, 2011). Specifically, CXCR7 makes it easier for EPC promoters to stay on the endothelium, to penetrate the area of angiogenesis, and to enhance the stability of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…6 The numbers of circulating EPCs have been shown to be increased in malignant diseases such as breast cancer, ovarian cancer, nonsmall cell lung cancer and lymphoma. [7][8][9][10][11][12] The kinetics of circulating EPCs and endothelial cells in response to antiangiogenic treatment have been studied in animal models. 2 There is evidence that metronomic chemotherapy and inhibitors of the VEGFR signalling pathway can suppress circulating EPC numbers.…”
Section: Introductionmentioning
confidence: 99%